CCAFS and CIAT, with support from USAID, successfully co-designed, developed and established the Althelia Biodiversity Fund to protect, restore, improve biodiversity and ecosystems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS and CIAT, with support from USAID, successfully co-designed, developed and established the Althelia Biodiversity Fund for Brazil, which is an impact investment fund targetting US$100m of investment which is focused on reducing deforestation, reducing emissions, building resilient livelihoods and protecting critical biodiversity. CIAT/CCAFS acts as a cornerstone investor and sits on the advisory board. Although established in September 2019, some initial investments are already being made with sustainable businesses in the Brazilian Amazon.